Assessment of CNS depressant activity of Nypa Fruticans Wurmb fruit pulp - Anika, Tasmim Farhana (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Pharmacy, 2024.